Diagnóstico hidrossedimentológico da bacia do arroio Cadena - Santa Maria/RS - Ilha, Róbson (2014)
The steady growth of cities along with the urbanization process has caused major changes in the natural environment, being part of the problem is a result of lack of knowledge of the dynamics that natural processes have. In the city of Santa Maria the population density and expansion process of the urban area were responsible for several modifications, among which we can cite the replacement of vegetation with pavements, changes in the form of relief, pollution of water resources and the various changes in drainage channels. Thus, studies of sediment loads in urban rivers are absolutely necessary to generate knowledge and appropriate technology development to minimize impacts to the environment. The aim of this study was to evaluate the relationships, the spatial and temporal behavior of hydrosedimentological processes in the watershed of the stream Cadena - Santa Maria / RS. The study area is the portion of the watershed of the stream with Cadena flow in Irmã Dulce section and two basins built this. Flow measurements and collecting suspended sediments in three locations along the canal for a spatial analysis of the data were performed. Temporal analysis were considered in the data obtained from Walter Jobim section that had one limnigraf. Sought to identify the main variables related to rain and the flow that control the transport of suspended sediment in the events in the basin. Pearson's coefficient was used to make this check, followed by an attempt to indicate a statistical model. The Cadena stream showed a high content of organic matter present in the samples reaching a value of 88% of the total suspended load. In eight of the twelve events monitored the concentration of organic matter was higher in the most downstream section, indicating an increase along the channel. Rainfall is less influential in the regime of flows when it is lower than your average (137mm), suggesting that in this situation the contributions coming from the urban drainage and sewer systems begin to exert greater influence under the regime of flow. During the study period the stream Cadena no tendency to erosion or deposition of sediment. It was observed that in the months from September to November there is a significant increase in sediment yield in the basin, a phenomenon that is part of the intra-annual climate variability in the region. The variables related to flow and rainfall events analyzed showed a good correlation with the concentration of suspended sediment measured (Cssmeasured). The simple regression model between Qmax and Cssmeasured showed a coefficient of determination (R ²) of 0.78, suggesting that the maximum flow is a good indicator of the transport of suspended sediment in the basin study.